Another look at motivating – and retaining – salespeople. Issue 4 (4th December 2018) - Lai, Christine Jaushyuam; Gelb, Betsy D.
Abstract : Purpose: This study aims to investigate to what extent salespeople are satisfied, dissatisfied or neither with various aspects of their job in ways predicted by the "two-factor model" assocating satisfaction with recognition and personal growth but not "hygiene factors." It further investigates which aspects of the salesperson's job are most strongly associated with commitment to the organization – or intention to leave. Design/methodology/approach: Interviewers gathered data from 176 salespeople in 154 companies. Those data were analyzed to identify aspects of the salesperson's job that are satisfiers, dissatisfiers or prompt indifference. The data were then correlated with the extent to which salespeople expressed commitment to their organization – and the extent to which they expressed likelihood of leaving their current job. Findings: Aspects of the salesperson's job do cluster into categories associated with the two-factor theory: satisfiers, dissatisfiers and other "hygiene factors" that are neither. However, two deviations from the theory appear. Pay is a satisfier, contrary to the assumptions behind the model, and factors beyond those intrinsic to the salesperson are also satisfiers. Supporting relevance of the theory for salespeople, however, is the strong association of recognition/personal growth aspects of the job positively with organizational commitment and negatively with intention to leave. Research limitations/implications: Although the data come from a convenience sample of salespeople, the results can be useful. For example, consideration of new products and of mergers should take into account their impact on salesperson satisfaction and dissatisfaction as motivational issues. Originality/value: This study is broader in focus than previous work relating the two-factor theory to salespeople, providing more confidence in the generalizability of the results.